Decision making and decision communication in an engineer based organization - Mykkänen, Markus (2010)
The purpose of this thesis was to examine how decisions are defined, made and communicated in an engineer based working community. These processes in this study are reviewed from the point of view of organizational communication. This study gathers information about how organizations define decisions, how they use information and how it affects the decision making in individual, group and organizational level. The target organization for this thesis was a local automation engineering department of Metso Paper. Decision making and decision communication were studied using mixed method. The superiors of the organization were interviewed and the employees answered a questionnaire. The results show that even decisions have no single definition, decision making and communication in automation engineering department is highly based on information and facts. Superiors and employees of organization prefer more face-to-face communication and email in decision communication. Combined with theoretical background this thesis show that decision communication is the backbone of the organization and organizational communication.